Investigating the Role of Volitional and Motivational Factors for Postgraduate Students’ Self-Regulated Learning in Academic Reading - Dewi, Annisa Satriani; Kuswandono, Paulus (Universitas Negeri Semarang, 2024)
Academic readings are meaningful and useful sources for academic writing. Both of them are inextricably intertwined. Postgraduate students need to read a lot of academic reading in order to get new insight and knowledge that will be useful for writing academic journals. In order to be successful in reading academic materials, postgraduate students need to apply metacognitive strategies. One of them is being self-regulated learners. There are many factors that promote good self-regulation. Two of them are motivation and volition. Using a mixed-methods explanatory framework, this research aimed to investigate how postgraduates self-regulate themselves in academic readings and to what extent motivational and volitional factors contribute to postgraduate students’ self-regulation in academic reading. The data was gathered through questionnaires completed by 31 postgraduate students and interviews with four chosen students. The findings found that most postgraduate students have motivational and volitional factors that influence their reading habits. It was shown that postgraduate students attributed self-regulated learning to their academic reading. Additionally, it was revealed that self-regulated learning showed a positive, significant, and moderate correlation with motivation (r=.355) as well as a positive, significant, and moderate correlation with volition (r=.456). The study found that academic reading requires postgraduate students to have strong self-regulated learning, motivation, and volitional strategies. Even though the results of the measurement were relatively positive, help from others was still needed, such as from the universities and master’s program lecturers, especially when it came to encouraging students to establish self-regulated learning habits. This study may be useful to the university and master’s program lecturers.